A split-Chevron-Notched-Beam sandwich specimen for fracture toughness testing of bonded interfaces - Lubauer, Julia; Belli, Renan; Lorey, Tony; Max, Stefanie; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
The realization that the use of strength tests as a means to probe the bonding performance of adhesive systems to dental restorative materials suffers from inherent drawbacks has shifted efforts towards devising viable and valid fracture toughness test for that purpose. Here we introduce a new procedure to produce split-Chevron-Notched-Beam specimens that need not undergo sawing or notching after bonding, thus sparing the interface from pre-stresses. We evaluate the formal geometric factor considering the influence of the use of different materials having different elastic properties, and show that the results obtained fall within reasonable ranges measured by other established compliance calibrated methods. We demonstrate the application of this new approach for dentin-luting composite and zirconia-luting composite interfaces for different adhesive systems and pre-treatment procedures in order to probe the sensitivity of the method to different bond qualities.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Adhesion; Bonding; Chevron-notched-beam; Dentin; Fracture toughness; Zirconia

Atomic structure of ZrO2-doped Li2O–SiO2-based multi-component glasses revealed by molecular dynamics–reverse Monte Carlo modeling - Toyoda, R.; Usui, K.; Hirota, T.; Kimura, K.; Onodera, Y.; Cicconi, Maria Rita; Belli, Renan; Brehl, Martin; Lubauer, Julia; Lohbauer, Ulrich; Tajiri, H.; Ikeda, K.; et al. (Journal of Non-Crystalline Solids, 2023)
Structural model of ZrO2-doped Li2O–SiO2-based multi-component glass, which is developed as a mother material for high-strength glass-ceramics, is constructed by the molecular dynamics–reverse Monte Carlo (MD–RMC) method based on anomalous X-ray and neutron scattering data. In particular, we have succeeded in extracting reliable local structural information around Zr from the MD–RMC model. It was found that a significant fraction of edge-sharing structural units was formed around Zr–O and Li–O polyhedra, resulting in a densely packed configuration of O atoms. This configuration was manifested by a very sharp principal peak in the neutron scattering data. Our model suggested that both the Zr and Li ions are incorporated in the glass as distorted ZrO6 octahedra and distorted LiO4 tetrahedra, respectively. These structural features are discussed in terms of the crystallization behavior of this material.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Anomalous X-ray scatteirng; Glass-ceramics; Molecular dynamics simulation; Neutron scattering; Reverse Monte Carlo

Concurrent kinetics of crystallization and toughening in multicomponent biomedical SiO2-Li2O-P2O5-ZrO2 glass-ceramics - Lubauer, Julia; Belli, Renan; Petschelt, Anselm; Cicconi, Maria Rita; Hurle, Katrin; Lohbauer, Ulrich (Journal of Non-Crystalline Solids, 2021)
We investigate here the crystallization kinetics of two pre-crystallized multicomponent dental glass-ceramics (IPS e.max® CAD, Ivoclar-Vivadent; Suprinity® PC, Vita Zahnfabrik) by interrupting the heat treatment at different periods of the non-isothermal and isothermal stage at 840°C. Differential scanning calorimetry (DSC) was used to characterize the crystallization peaks of the pre-crystallized and the base glass, and dilatometry was used to determine the coefficient of thermal expansion and Tg after different times at the maximum temperature. The evolution of crystallinity was tracked by XRD, while the evolution of fracture toughness was obtained by the ball-on-three-balls surface crack in flexure method. The change in microstructural features was made visible using FE-SEM. We show that the isothermal stage is dominated by the transformation of Li2SiO3 in Li2Si2O5, inducing the impingement of nanocrystals into clusters. The residual glass became thereby less polymerized. The kinetics of toughening followed closely the evolution of crystallinity in both systems.
CRIS-Team Scopus Importer:2021-02-12

Fatigue Threshold R-Curves for Dental Lithium Disilicate Glass–Ceramics - Lubauer, Julia; Lohbauer, Ulrich; Belli, Renan (Journal of Dental Research, 2023)
Chemical and mechanical fatigue degradation in ceramic materials is generally inconspicuous yet ubiquitous, to the effect that clinical fractures still consist of the main cause of failure in all-ceramic restorations. Implications of this span wide, from a reduced survival prognosis for the affected teeth, including more frequent and increasingly invasive procedural interventions, to the financial burden borne by individuals and health care systems. To suffice as an effective corrective, restoration lifetimes need only to be extended so to outlive the patient. That opens a box of problems from a materials science standpoint, entailing inherent deficiencies of brittle materials to resist mechanical and environmental challenges. Efforts in developing more damage-tolerant and fatigue-resistant restoratives go thus hand in hand with understanding intrinsic mechanisms of crack growth behavior under conditions that simulate the oral environment. Here we developed experiments using size-relevant sharp precracked specimens with controlled size and geometry (truncated semielliptical crack in the surface-crack-in-biaxial-flexure method) to establish a relationship between crack size and strength. The tangent method was used to construct envelopes for the quasi-static resistance curves (R-curves), which served as template for deriving residual cyclic R-curve analogs. By means of experimentally obtained stress–cycle curves, lifetime and fatigue parameters were employed within a mechanistic framework to reveal constitutive toughening mechanisms during subcritical growth under cyclic loading in a wet environment. Using 3 modern dental lithium disilicate glass–ceramics, we demonstrate the extent of R-curve degradation up to a threshold of 10 million cycles ( 30 y in service) and draw parallels between the scope of fatigue degradation and the size of the microstructural units responsible for toughening mechanisms in glass–ceramic materials. Our results indicate that larger microstructural elements endow glass–ceramics with a higher reaching quasi-static R-curve at the onset but degrading more rapidly to comparable levels of lithium disilicates having submicrometric and nanometric crystal phases.
CRIS-Team Scopus Importer:2023-07-28
Keywords: CAD–CAM; ceramics; flexural strength; lithia disilicate; mechanical tests; stress fracture

Glass science behind lithium silicate glass-ceramics - Lohbauer, Ulrich; Fabris, Débora Cristina Niero; Lubauer, Julia; Abdelmaseh, Samuel; Cicconi, Maria Rita; Hurle, Katrin; de Ligny, Dominique; Götz-Neunhoeffer, Friedlinde; Belli, Renan (Dental Materials, 2024)
Objectives: Lithium silicate-based glass ceramics have evolved as a paramount restorative material in restorative and prosthetic dentistry, exhibiting outstanding esthetic and mechanical performance. Along with subtractive machining techniques, this material class has conquered the market and satisfied the patients’ needs for a long-lasting, excellent, and metal-free alternative for single tooth replacements and even smaller bridgework. Despite the popularity, not much is known about the material chemistry, microstructure and terminal behaviour. Methods: This article combines a set of own experimental data with extensive review of data from literature and other resources. Starting at manufacturer claims on unique selling propositions, properties, and microstructural features, the aim is to validate those claims, based on glass science. Deep knowledge is mandatory for understanding the microstructure evolution during the glass ceramic process. Results: Fundamental glass characteristics have been addressed, leading to formation of time-temperature-transformation (TTT) diagrams, which are the basis for kinetic description of the glass ceramic process. Nucleation and crystallization kinetics are outlined in this contribution as well as analytical methods to describe the crystalline fraction and composition qualitatively and quantitatively. In relation to microstructure, the mechanical performance of lithium silicate-based glass ceramics has been investigated with focus on fracture strength versus fracture toughness as relevant clinical predictors. Conclusion: Fracture toughness has been found to be a stronger link to initially outlined manufacturer claims, and to more precisely match ISO recommendations for clinical indications.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Clinical indication; Crystallization; Flexural strength; Fracture toughness; Glass ceramic; Lithium silicate; Nucleation; Residual stress

Grasping the Lithium hype: Insights into modern dental Lithium Silicate glass-ceramics - Lubauer, Julia; Belli, Renan; Peterlik, Herwig; Hurle, Katrin; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: Lithium-based glass-ceramics are currently dominating the landscape of dental restorative ceramic materials, with new products taking the market by storm in the last years. Though, the difference among all these new and old products is not readily accessible for the practitioner, who faces the dilemma of reaching a blind choice or trusting manufacturers' marketing brochures. To add confusion, new compositions tend to wear material terminologies inherited from vanguard dental lithium disilicates, disregarding accuracy. Here we aim to characterize such materials for their microstructure, crystalline fraction, glass chemistry and mechanical properties. Methods: Eleven commercial dental lithium-based glass ceramics were evaluated: IPS e.max (R) CAD, IPS e.max (R) Press, Celtra (R) Duo, Suprinity (R) PC, InitialTM LiSi Press, InitialTM LiSi Block, Amber (R) Mill, Amber (R) Press, N!CE (R), Obsidian (R) and CEREC TesseraTM. The chemical composition of their base glasses was measured by X-Ray Fluorescence Spectroscopy (XRF) and Inductive Coupled Plasma Optical Emission Spectroscopy (ICPOES), as well as the composition of their residual glass by subtracting the oxides bound in the crystallized fraction, characterized by X-Ray Diffraction (XRD) and Rietveld refinement, and quantified accurately using the G-factor method (QXRD). The crystallization behavior is revealed by differential scanning calorimetry (DSC) curves. Elastic constants are provided from Resonant Ultrasound Spectroscopy (RUS) and the fracture toughness measured by the Ball-on-Three-Balls method (B3B- K Ic). The microstructure is revealed by fieldemission scanning electron microscopy (FE-SEM). Results: The base glasses showed a wide range of SiO2 /Li2O ratios, from 1.5 to 3.0, with the degree of depolymerization dropping from 1/2 to 2/3 of the initial connectivity. Materials contained Li2SiO3+Li3PO4, Li2SiO3+Li3PO4+Li2Si2O5, Li2Si2O5+Li3PO4+ Cristobalite and/or Quartz and Li2Si2O5+Li3 PO4+LiAlSi2O6, in crystallinity degrees from 45 to 80 vol%. Crystalline phases could be traced to their crystallization peaks on the DSC curves. Pressable materials and IPS e.max (R) CAD were the only material showing micrometric phases, with N!CE (R) and InitialTM LiSi Block showing solely nanometric crystals, with the rest presenting a mixture of submicrometric and nanometric particles. Fracture toughness from 1.45 to 2.30 MPa root m were measured, with the linear correlation to crystalline fraction breaking down for submicrometric and nanometric crystal phases. Significance: Dental lithium-based silicate glass-ceramics cannot be all put in the same bag, as differences exist in chemical composition, microstructure, crystallinity and mechanical properties. Pressable materials still perform better mechanically than CAM/CAM blocks, which loose resistance to fracture when crystal phases enter the submicrometric and na-nometric range (c) 2021 The Academy of Dental Materials. Published by Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2022-03-04

Inner marginal strength of CAD/CAM materials is not affected by machining protocol - Lubauer, Julia; Belli, Renan; Schünemann, Fernanda H.; Matta, Ragai; Wichmann, Manfred; Wartzack, Sandro; Völkl, Harald; Petschelt, Anselm; Lohbauer, Ulrich (Biomaterial Investigations in Dentistry, 2021)
Purpose Here we aimed to compare two machining strategies regarding the marginal strength of CAD/CAM materials using a hoop-strength test in model sphero-cylindrical dental crowns, coupled with finite element analysis. Materials and Methods Five CAD/CAM materials indicated for single posterior crowns were selected, including a lithium disilicate (IPS e.max® CAD), a lithium (di)silicate (Suprinity® PC), a polymer-infiltrated ceramic scaffold (Enamic®), and two indirect resin composites (Grandio® Blocs and Lava™ Ultimate). A sphero-cylindrical model crown was built on CAD Software onto a geometrical abutment and machined using a Cerec MC XL system according to the two available protocols: rough-fast and fine-slow. Specimens were fractured using a novel hoop-strength test and analyzed using the finite element method to obtain the inner marginal strength. Data were evaluated using Weibull statistics. Results Machining strategy did not affect the marginal strength of any restorative material tested here. Ceramic materials showed a higher density of chippings in the outer margin, but this did not reduce inner marginal strength. IPS e.max® CAD showed the statistically highest marginal strength, and Enamic® and Lava™ Ultimate were the lowest. Grandio® Blocs showed higher performance than Suprinity® PC. Conclusions The rough-fast machining strategy available in Cerec MC XL does not degrade the marginal strength of the evaluated CAD/CAD materials when compared to its fine-fast machining strategy. Depending on the material, resin composites have the potential to perform better than some glass-ceramic materials.
Keywords: CAD/CAM; strength; finite element

Intricacies involving the evaluation of fracture toughness obtained by the surface-crack-in-flexure method - Lubauer, Julia; Lohbauer, Ulrich; Henrich, Martina; Munz, Maximilian; Lube, Tanja; Belli, Renan (Journal of the American Ceramic Society, 2022)
Among the several methods available for the measurement of the fracture toughness (KIc), the surface-crack-in-flexure (SCF) has the advantages of being based on an easy-to-produce short (application relevant) crack size of defined geometry with a naturally sharp crack tip. The production of ready-to-test cracked specimens is fast and uncomplicated, rendering accurate results with low scatter. However efficient and reliable, the procedural steps for the obtainment of a valid crack need revisions, especially on aspects concerning the polishing depth, the removal of lateral cracks, the obtainment of an appropriate crack geometry, and the use of adequate solutions for the geometry factor. In this study we attend to these issues by systematically polishing a large number of specimens of two ceramic materials having very distinct subsurface Knoop crack systems to assess the effect of remnants of lateral cracks. By evaluating the geometry factor of the median precrack along the entire crack front, we provide valid ranges for the crack geometry regarding the crack-surface intersection angle as resulting from the polishing depth, extending the applicability of the Strobl et al. solution to shallow cracks in detriment of the Newman and Raju formula that is poised to overestimations of KIc of up to 10%. Our results debunk the belief that lateral cracks affect the obtained KIc, but demonstrate the necessity of a minimum polishing depth for the attainment of valid crack geometries.
CRIS-Team Scopus Importer:2022-08-12
Keywords: fracture toughness; Knoop indentation; lateral cracks; lithium disilicate; silicon nitride; stress intensity factor; surface-crack-in-flexure

Nucleation mechanisms in a SiO2-Li2O-P2O5-ZrO2 biomedical glass-ceramic: Insights on crystallisation, residual glasses and Zr4+ structural environment - Cicconi, Maria Rita; Belli, Renan; Brehl, Martin; Lubauer, Julia; Hayakawa, T.; Kimura, K.; Hirota, T.; Usui, K.; Kohara, S.; Onodera, Y.; Lohbauer, Ulrich; Hayashi, K.; et al. (Journal of the European Ceramic Society, 2022)
In manufacturing reliable glass-ceramics, bulk chemistry and appropriate thermal treatments are critical points. To better understand the influence of nucleation parameters on the crystallisation behaviour and mechanical properties of multicomponent glass-ceramics, we studied the effects of time and temperature on phase stabilisation, the evolution of the crystal phases and physical properties of a Zr-rich lithium-silicate having a SiO2/Li2O molar ratio < 2. Here, we also provide insights into the structural environment of Zr4+ at the early stage of nucleation by Anomalous X-ray Scattering (AXS). By reverse-engineering a commercial material through remelting and sequential thermal treatments, we observed the strong effect of the nucleation temperature on the final mineral assemblage and of the volume fractions of the lithium-disilicate phase on the fracture toughness (KIc). Indeed, the KIc value was increased from ∼0.8 MPa.m½ in the pristine glass up to ∼ 2 MPa.m½, if compared to the original commercial material exhibiting a KIc value of 1.6 MPa.m½. Furthermore, the synthesis of residual glasses at different stages of the thermal treatments allowed us to observe the changes in the glass network structure and properties. AXS was used to extract the contribution exclusively coming from Zr for different nucleation steps. The differential pair distribution functions ΔZrg(r) show two distinct peaks at ∼2.10 Å and 3.44 Å, respectively associated with Zr-O and Zr-Zr/Zr-Si correlations with the formation of edge sharing in addition to corner sharing polyhedra. It was discerned the occurrence of (sub)nano-sized clusters enriched in Zr. These local clusters do not show changes during the different thermal treatments, either for higher temperatures or longer times. No Zr phases are stabilised in the crystallised materials, suggesting that these clusters do not evolve above the critical nucleus size. All evidence points to a highly heterogeneous environment and the coexistence of three structural regions i) (sub)nano Zr-clusters, ii) P enriched μ-areas, iii) residual silicate glass. The evolution and spatial distribution of these units influence the final properties.
CRIS-Team Scopus Importer:2022-01-21
Keywords: AXS; Raman; Residual glasses; Structure; Toughness; Zr

On the assignment of quartz-like LiAlSi2O6 - SiO2 solid solutions in dental lithium silicate glass-ceramics: Virgilite, high quartz, low quartz or stuffed quartz derivatives? - Hurle, Katrin; Lubauer, Julia; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: Here we aim to provide a background on X-Ray Diffraction analysis of quartz-like crystal structures with varying amounts of Al3+ and Li+ substitution, existing confusions on their nomenclature and its implications for novel lithium silicate glass-ceramics. Methods: We reviewed the literature dealing with modifications of the quartz crystal structure and their stuffed LiAlSi2O6 derivates, LiAlSi2O6 – SiO2 solid solutions, the terminology of such phases and criteria used to define the structure known as virgilite. Based on this information, we attempted to allocate the quartz-like phases found in CEREC TesseraTM, InitialTM LiSi Block and Amber® Mill in the range of LiAlO2 - SiO2 solid solutions. For this purpose, their lattice parameters obtained from Rietveld refinement were compared with the lattice parameters of members of the corresponding solid solutions with defined SiO2 molar fraction found in the literature. Results: Based on the lattice parameters available for low quartz, high quartz and its stuffed derivatives, including LiAlSi2O6 and the mineral virgilite, a plot of the a- and c-parameters vs. the mol% SiO2 related to LiAlO2 was constructed with the literature data and the data found for the three dental lithium silicates. As per the definitions of virgilite as either LixAlxSi3-xO6, with 0.5 < x < 1 or especially as members of the LiAlSi2O6 – SiO2 solid-solution series with more than 50 mol% LiAlSi2O6, the crystal structures in CEREC TesseraTM, InitialTM LiSi Block and Amber® Mill failed to fall within the ranges of mol% SiO2 confined for virgilite. Significance: Based on available literature and definitions, the quartz-like phases found in the three dental lithium silicates should be addressed as stuffed (probably low) quartz solid solutions instead of “virgilite”. However determined by mineralogical practices, the term “virgilite” for parts of the LiAlSi2O6 – SiO2 solid solution is ambiguous and can be considered as arbitrary.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Crystal; Glass-ceramics; Lithium silicate; Quartz; Virgilite; X-ray diffraction

Reply to Quinn GD, Salem JA, Swab JJ. Comment On: Lubauer J, Lohbauer U, Henrich M, Munz M, Lube T, Belli R. Intricacies involving the evaluation of fracture toughness obtained by the surface-crack-in-flexure method. J Am Ceram Soc. 2022;105(12):7582-7599. - Belli, Renan; Lubauer, Julia; Lohbauer, Ulrich; Henrich, Martina; Munz, Maximilian; Lube, Tanja (Journal of the American Ceramic Society, 2023)
CRIS-Team Scopus Importer:2023-06-30

Resistance-curve envelopes for dental lithium disilicate glass-ceramics - Lubauer, Julia; Ast, Johannes; Göken, Mathias; Merle, Benoit; Lohbauer, Ulrich; Belli, Renan (Journal of the European Ceramic Society, 2022)
Recent investigations on the mechanics of dental lithium disilicates have gathered mounting evidences of a probable R-curve behavior. Here we use an indirect approach to obtain the contours of the R-curve using the relationship between strength and initial crack size obtained from quasi-static fracture toughness tests. The tangent condition formed by the multiple K I,appl (ai,j) curves give a smoothened polygonal envelope for the R-curves. The R-curves obtained this way were extended toward an initial value at the onset of stable crack extension, obtained hereusing a microcantilever specimen featuring a sharp notch produced by focused-ion-beam milling. The presence of an R-curve effect was confirmed for the three evaluated lithium disilicates, being more pronounced for the injection-molded material having an oriented elongated Li2Si2O5 microstructural architecture, with crystal fraction playing an important role for low-aspect ratio randomly-oriented microstructures.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Dental ceramics; Focused ion beam milling; Fracture toughness; Lithium silicate; Micro-scale; R-curve

Speed-sintering and the mechanical properties of 3–5 mol% Y2O3-stabilized zirconias - Lubauer, Julia; Schuenemann, Fernanda Haverroth; Belli, Renan; Lohbauer, Ulrich (Odontology, 2023)
Ever faster workflows for the fabrication of all-ceramic restorations are of high economic interest. For that purpose, sintering protocols have been optimized for use in modern sintering furnaces, the so-called speed-sintering. However, conventional furnaces are still the most widely used equipment to sinter zirconia restorations. In this in-vitro study, we evaluated the feasibility of a speed-sintering protocol using a conventional sintering furnace to sinter different dental zirconias (stabilized with 3 mol% up to 5.4 mol% Y2O3) in comparison to a conventional sintering program. The properties evaluated were Young’s modulus, Poisson’s ratio, density, biaxial flexural strength, and fracture toughness. We show here that despite differences being dependent on material, the physical and mechanical properties of speed-sintered zirconia are comparable to those obtained by the conventional sintering.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Flexural strength; Mechanical tests; Yttria-stabilized tetragonal zirconia

Toughening by revitrification of Li2SiO3 crystals in Obsidian® dental glass-ceramic - Lubauer, Julia; Hurle, Katrin; Cicconi, Maria Rita; Petschelt, Anselm; Peterlik, Herwig; Lohbauer, Ulrich; Belli, Renan (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
As a predominantly lithium-metasilicate-containing glass-ceramic, Obsidian® (Glidewell Laboratories, USA) has a peculiar composition and microstructure among other dental lithium silicates, warranting an evaluation of the crystallization process to establish relationships between microstructural evolution and mechanical properties. Blocks of the pre-crystallized material were processed into slices measuring 12 × 12 × 1.5 mm3 and subjected to the mandatory crystallization firing by interruption the heating ramp at temperatures between 700 °C and 820 °C (dwell time between 0 min and 10 min). The crystallization peaks of the base and the pre-crystallized glass were obtained by differential scanning calorimetry (DSC). The coefficient of thermal expansion and the glass transition temperature were derived from differential thermal analysis (DTA). X-ray diffraction (XRD) was performed to quantify and characterize the crystal phase fraction, whose microstructural changes were visualised using FE-SEM. The ball-on-three-balls surface crack in flexure method was used to track the evolution of fracture toughness. The microstructural evolution during crystallization firing was characterized by two regimes of growth: (i) the progressive revitrification (dissolution) of the 5 μm-sized Li2SiO3 polycrystals manifested at the boundaries of nanometric single coherent scattering domains (CSDs); (ii) the non-isothermal period is marked by an Ostwald ripening process characterized by the growth of the single crystalline structures into 0.5 μm polycrystals. The decrease in the crystal fraction of Li2SiO3 crystals from 41 vol.% to 37 vol.% is accompanied by the formation of a small amount of Li3PO4 (6 vol.%), maintaining the total crystal phase fraction mostly constant. The KIc accompanied the reverse trend of crystallinity, departing from 1.63 ± 0.02 MPa√m at the pre-crystallized stage to 1.84 ± 0.06 MPa√m after 10 min at 820 °C in a linear trend. Toughening appeared counter-intuitive in view of the decreasing crystal fraction and size, to rather relate to the relaxation of the residual stresses in the interstitial glass due to the spheroidization of the initially anisotropic, elongated Li2SiO3 crystals into round, nearly equiaxed particles, as let suggest from the disappearance of the extensive microcracking.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Crystallization; Dental; Fracture toughness; Glass-ceramic; Mechanical properties; X-ray Diffraction